Long quasi-periodic oscillations of the faculae and pores - Riehokainen A; Strekalova P; Solov'ev A; Smirnova V; Zhivanovich I; Moskaleva A; Varun N (EDP SCIENCES S A, 2022)
Aims. The main goal of this work is to analyze the structural and temporal evolution of small-scale magnetic structures (SSMSs) observed in the solar atmosphere, such as solitary faculae and pores, and reveal long quasi-periodic oscillations of these structures.Methods. The statistical method of regression analysis and the wavelet transform were used to obtain the periods of oscillations and dependences between the parameters of magnetic structures and periods of oscillations.Results. Long-period oscillations with periods in the interval of 18-260 min are found for the structurally stable phase of SSMSs at the level of the solar photosphere. These long-period oscillations were interpreted as natural oscillations of the structurally stable long-lived magnetic structures around their equilibrium position. These oscillations, which are of similar nature, are observed in the chromospheric bright formations associated with photospheric SSMSs. Dependences between the magnetic field and the continuum intensity of the facula elements were found. It is shown that the continuum intensity of a SSMS decreases when its magnetic field increases.